PENDUDUK DAN PEMBANGUNAN PERUMAHAN DI JABODETABEK : TANTANGAN PENGEMBANGAN MEGAPOLITAN JAKARTA - Rusli Cahyadi; Gusti Ayu Ketut Surtiari (Research Centre for Population, Indonesian Institute of Sciences, 2009)
Megapolitan Jakarta is an urban planning concept which integrate to Jakarta and its surrounding cities (i.e. Bogor, Depok, Tangerang, and Bekasi). The concept also included the spread effect of development growth and welfare. The most important issue related to megapolitan development were the increasing number of population and of housing demand. The increasing number of Jakarta s population is already reached its maximum capacity whereas they were no space for housing anymore in Jakarta. Finally, most of people who work in Jakarta have to settle in surround city of Jakarta. But, the problem is economic characteristics of people and the housing supply were mismatched. People who lived in the Jakarta s surrounding area were dominated by people who live in middle-lower level of socioeconomic condition, on the other hand, housing supply was dominated by housing for middle-upper socio-economic level. This mismacth was considered as the biggest drawbacks for the development of Jakarta Megapolitan.Keywords: Population; housing; megapolitant; Jabodetabek